Green economy as an environment-based framework for Indonesia's economic reposition structure - Evi Susanti Tasri; Syafruddin Karimi (Economic Journal of Emerging Markets, 2014)
Economic development should consider the negative effects it creates. This will help to achieve a sustainable economic development. The green economic conceptcan be a solution to development process that works on natural resources conservation. This paper proposes a discriminant analysis to describe the green economic development. It analyses a group of countries, classified by their income levels. The analysis result suggests that environment factors such asemissions and area of the forest are important variables.